Birth and decay of the Chilean Constitutional Tribunal (1970–1973): The irony of a wrong electoral prediction - Verdugo, Sergio (Oxford University Press, 2017)
Scholars debate about why constitution-makers create constitutional courts, and what the conditions are for making these tribunals politically relevant. This article examines how the understudied Chilean 1970–1973 Constitutional Tribunal has contributed to this discussion. That Tribunal was created in 1970, through an error made by constitution-amenders who believed that someone else was going to be elected president. Although the Tribunal generally benefited the unexpectedly elected president (Allende), it finally lost its relevance because of its refusal to alleviate a significant political conflict. Judicial review theories based on rights and political competition are not applicable to the Chilean case. The separation of powers theory, which claims that constitutional courts develop because of their function in solving inter-branch disputes, partly explains the creation of the Tribunal. However, the Chilean example suggests that that theory does not apply in highly controversial contexts.
Keywords: 56 Ciencias Jurídicas y Derecho; ODS 16 - Paz, justicia e instituciones sólidas